Responses of schoolchildren with asthma to recommendations to reduce desert dust exposure: Results from the LIFE-MEDEA intervention project using wearable technology - Kouis, Panayiotis; Michanikou, Antonis; Galanakis, Emmanouil; Michaelidou, Eleni; Dimitriou, Helen; Perez, Julietta; Kinni, Paraskevi; Achilleos, Souzana; Revvas, Efstathios; Stamatelatos, Gerasimos; Zacharatos, Harris; Savvides, Chrysanthos; et al. (My University, 2023)
Current public health recommendations for desert dust storms (DDS) events focus on vulnerable population groups, such as children with asthma, and include advice to stay indoors and limit outdoor physical activity. To date, no scientific evidence exists on the efficacy of these recommendations in reducing DDS exposure. We aimed to objectively assess the behavioral responses of children with asthma to recommendations for reduction of DDS exposure. In two heavily affected by DDS Mediterranean regions (Cyprus & Crete, Greece), schoolchildren with asthma (6-11 years) were recruited from primary schools and were randomized to control (business as usual scenario) and intervention groups. All children were equipped with pedometer and GPS sensors embedded in smartwatches for objective real-time data collection from inside and outside their classroom and household settings. Interventions included the timely communication of personal DDS alerts accompanied by exposure reduction recommendations to both the parents and school-teachers of children in the intervention group. A mixed effect model was used to assess changes in daily levels of time spent, and steps performed outside classrooms and households, between non-DDS and DDS days across the study groups. The change in the time spent outside classrooms and homes, between non-DDS and DDS days, was 37.2 min (pvalue = 0.098) in the control group and -62.4 min (pvalue < 0.001) in the intervention group. The difference in the effects between the two groups was statistically significant (interaction pvalue < 0.001). The change in daily steps performed outside classrooms and homes, was -495.1 steps (pvalue = 0.350) in the control group and -1039.5 (pvalue = 0.003) in the intervention group (interaction pvalue = 0.575). The effects on both the time and steps performed outside were more profound during after-school hours. To summarize, among children with asthma, we demonstrated that timely personal DDS alerts and detailed recommendations lead to significant behavioral changes in contrast to the usual public health recommendations.
Keywords: Asthmatic children; Desert dust storms; Global positioning system; Outdoor exposure; Physical activity; Wearable sensors